Faktor Yang Mempengaruhi Keberanian Siswa Madrasah Tsanawiyah Ar Raudhah Pada Aktivitas Meroda Dalam Pembelajaran Pendidikan Jasmani - Jodi Dermawan; Saepul Mamun; Rustam Efendi (Peneliti.net, 2022)
This research was conducted based on the existence of problems in the physical education learning process, especially in the learning of floor gymnastics for wheeling activities, where many of the students did not dare to do wheeling activities. This research method is a research with a qualitative approach with a case study method to be able to understand the factors that influence the courage of the students of Madrasah Tsanawiyah Ar Raudhah in wheeling activities in physical education learning. The results of the research on factors that affect the courage of Madrasah Tsanawiyah Ar Raudhah students in wheeling activities in physical education learning are dependent on the way the teacher delivers the material, the methods used in teaching and learning activities, facilities and infrastructure, direct practice and encouragement from students and encouragement from outside